2014
DOI: 10.1007/s10162-014-0442-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opening Middle-Ear Cavity on Vibrations of Gerbil Tympanic Membrane

Abstract: This paper presents in vivo experimental measurements of vibrations on the pars flaccida, along the manubrium and at several points on the pars tensa in the gerbil with open middle-ear cavity. The effects of progressive opening of the middle-ear cavity are presented, with up to five different extents of opening. In all manubrial, pars-tensa and pars-flaccida responses, opening the cavity causes an increase in the low-frequency magnitude and a shift of the main middle-ear resonance to lower frequencies and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The pars flaccida in the model shows responses similar to those measured by Rosowski et al (1997) and Maftoon et al (2014). Our sensitivity analysis shows that the resonance of the pars flaccida shifts to lower frequencies as its Young's modulus or thickness decreases.…”
Section: Model Responsessupporting
confidence: 84%
See 4 more Smart Citations
“…The pars flaccida in the model shows responses similar to those measured by Rosowski et al (1997) and Maftoon et al (2014). Our sensitivity analysis shows that the resonance of the pars flaccida shifts to lower frequencies as its Young's modulus or thickness decreases.…”
Section: Model Responsessupporting
confidence: 84%
“…Furthermore, this study does not try to explore the model response in terms of ossicular vibrations in detail: we have presented the displacements of the manubrium along only a single direction and only the piston component of the stapes displacement. Validation of the ossicular motion will require further study, taking into account the 3-D ossicular motions that have been reported by Decraemer et al 2007,2014) as well as the experimental manubrial motion results by Maftoon et al (2013Maftoon et al ( , 2014. A future study should investigate losses in the middle ear due to radiation impedance and to damping in different middle-ear structures, as well as middleear transmission and power flow from the TM to the cochlea.…”
Section: Study Approachmentioning
confidence: 87%
See 3 more Smart Citations